Central Europe and European monetary integration: a strategy for catching up - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
The Maastricht Treaty has augmented the preconditions that have to be fulfilled by ED applicants before a full membership can be achieved. Candidates have to prove that a participation in the European Monetary Union is a realistic possibility at least in the medium term. This paper explores the difficulties of the Visegrád countries to fulfill this monetary precondition. Apart from the convergence criteria, the cyclical correlation both within Central Europa and between Central and Western Europe is analysed. Based on that evidence, an early membership in the European Monetary System is proposed as an element of a promising EU membership strategy. Besides that, the potential role of a stabilization fund is discussed that could cushion asymmetric shocks hitting the Visegrád countries.
Keywords: 330